Confining Liquids on Silicon Surfaces to Lubricate MEMS - Leong,JY; Zhang,J; Sinha,SK; Holmes,A; Spikes,H; Reddyhoff,T (Tribology Letters, 2015)
Liquid lubrication may provide a solution tothe problem of high friction and wear in micro-electromechanicalsystems. Although the effectiveness of thisapproach has been demonstrated in laboratory-based frictiontests, practical constraints prevent it from being appliedin commercial devices. The main problem is how toposition the lubricant on a silicon surface in order to limitspreading and evaporation. This paper describes twotechniques to address this issue. First, low concentrationsof additives are used to promote autophobic behaviour.Tests’ results show that certain concentrations of bothmultiply alkylated cyclopentane and amine additives areeffective in halting the spread of hexadecane on silicon,and, in the latter case, cause the hexadecane drop to subsequentlyretract. The second approach involves applying amicro-contact printing technique previously used on goldsurfaces. Here, silicon surfaces are coated with octadecyltrichlorosilanemono-layers that are then selectively removed,using oxygen plasma, to leave regions ofcontrasting surface energy. Results from spin tests showthat surfaces treated in this way can anchor 1 ll drops ofhexadecane and water when forces of up to 22 and 230 lN,respectively, are applied.